Corrosight: web-based platform for real-time corrosion rate calculation and ffatigue assessmentin gas pipelines - Richard Liangson, Russell Spielberg; Ismail, Shahrom; Mahmud, Jamaluddin; Amir Hassan, Muhammad Taufik; Mohamad Assaat, Mohamad Faiz (2025)
Corrosight addresses critical corrosion-fatigue assessment challenges in gas pipeline operations. This web platform integrates API/ASME-compliant computational engines to enable: (1) real-time corrosion rate calculations via electrochemical models, (2) fatigue life prediction under cyclic loading, and (3) automated Fitness-for-Service reporting. Validated against 78 field cases, it reduces assessment time by 78% while maintaining ±0.12 mm/yr accuracy. The solution bridges capability gaps between onsite field engineers and design teams.